Peluang dan Tantangan Dari Pengaturan Indikasi Geografis di Indonesia - Theodore, Olivia; Daulay, Zainul; Elvardi, Jean (Nagari Law Review, 2023)
Geographical Indication is the new black in the world of intellectual property because of their very high commercialization potential, although they have not received as much attention as other intellectual property rights. In Indonesia, the regulations for Geographical Indication have been updated through Law Number 20 of 2016 concerning Trademarks and Geographical Indication (UU 20/2016) to be more in line with the provisions in Trade-Related Aspects of Intellectual Property Rights . Through this arrangement, it is expected that Indonesia can maximize the monetization of Geographical Indication by taking advantage of opportunities and overcoming existing challenges to encourage regional and national economic revival. Therefore this study raises two problem formulations, namely: (1) How are Geographical Indication regulated in Indonesia?; and (2) What are the opportunities and challenges of managing Geographical Indication in Indonesia?. This is a normative research using statutory, historical, comparative, and conceptual approaches with several interviews with related parties to sharpen the problem analysis. The resulting findings indicate that regarding the regulation of Geographical Indication in Indonesia there are several opportunities that can be utilized by producers and the public in the regions, namely, registration of Geographical Indication other than Agricultural Products, use of the national logo of Geographical Indication, registration of Geographical Indication abroad, follow-up of violations of Geographical Indication. Apart from that, there are also several challenges, namely, the lack of understanding of the registration process of Geographical Indication, the use of the 'logo' in the registration of Geographical Indication, the term 'User of Geographical Indication' in Law 20/2016.